CHEMISTRY OF THE SERPENTINIZATION OF KIMBERLITE - Yegorov K.N.; Bogdanov G.V.; Paradina L.F. (My University, 1990)
One of the important unsolved problems regarding the serpentinization of Kimberlite is the mineragenetic and chemical direction of this process in its various stages. We analyzed this development on a series of specimens from the Udachnaya-Vostochnaya kimberlite pipe, representing a gradual transition from original, unserpentinized rocks to completely altered kimberlite with a full set of secondary minerals. We identified five zones of hydrothermal metasomatic alteration of the kimberlite that varied in the extent of serpentinization, the ratios of the various types of serpentinite, and the percentages of the accessory minerals in the rock. The chemical composition of the serpentinite changed in this succession of zones. We determined the contents of pure lizardite and chrysotile chemically, concurrently with X-ray diffractometric and other analyses of the rock.